2018
DOI: 10.1002/hep.30066
|View full text |Cite
|
Sign up to set email alerts
|

TRUSS Exacerbates NAFLD Development by Promoting IκBα Degradation in Mice

Abstract: There is no effective treatment method for nonalcoholic fatty liver disease (NAFLD), the most common liver disease. The exact mechanism underlying the pathogenesis of NAFLD remains to be elucidated. Here, we report that tumor necrosis factor receptor-associated ubiquitous scaffolding and signaling protein (TRUSS) acts as a positive regulator of NAFLD and in a variety of metabolic disorders. TRUSS expression was increased in the human liver specimens with NAFLD or nonalcoholic steatohepatitis, and in the livers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 47 publications
1
4
0
Order By: Relevance
“…However, the increased AKT phosphorylation was accompanied with the unaltered sterol regulatory element binding transcription factor-1C (SREBP-1C) expression in SAA1-deficient murine liver. Consistent observations are also reported in other inflammation-driven NAFLD models, in which the inflammatory mediators have impact to enhance lipid synthesis [ 35 , 36 ]. The increase in NEFA and suppression of its metabolism in hepatocytes induced by SAA1 may promote the development of NASH.…”
Section: Discussionsupporting
confidence: 85%
“…However, the increased AKT phosphorylation was accompanied with the unaltered sterol regulatory element binding transcription factor-1C (SREBP-1C) expression in SAA1-deficient murine liver. Consistent observations are also reported in other inflammation-driven NAFLD models, in which the inflammatory mediators have impact to enhance lipid synthesis [ 35 , 36 ]. The increase in NEFA and suppression of its metabolism in hepatocytes induced by SAA1 may promote the development of NASH.…”
Section: Discussionsupporting
confidence: 85%
“…Interestingly, our recent study demonstrated that myeloid-derived growth factor (MYDGF), a protein secreted from bone marrow-derived monocytes and macrophages [ 10 ], improved IR and glucose-lipid metabolic profiles in diabetic mice [ 11 ]. Metabolic disorders have also been shown to be closely associated with NAFLD [ 12 , 13 ]. Therefore, in this study, we first aimed to ascertain whether MYDGF can modulate NAFLD and the possible underlying mechanisms, before exploring whether MYDGF serves as a factor involved in the crosstalk between bone marrow and liver that regulates liver fat metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…These findings suggest that TRPC3 and TRPC6 are unlikely to be implicated in liver dysfunction and fibrosis in NAFLD mouse models. 328 No effective therapy is available for NAFLD, and its exact pathogenesis remains to be elucidated. All these data indicate that TRP channels may be an interesting target for drug development for the treatment of NAFLD.…”
Section: Physiological Functions Of Trp Channelsmentioning
confidence: 99%